ANALISIS PENGARUH SEKTOR INDUSTRI TERHADAP DINAMIKA PERTUMBUHAN EKONOMI DI KOTA KEDIRI - Anggela Setiya Putri; Riko Setya Wijaya; Putra Perdana (Universitas Nias Raya, 2025)
This study aims to analyze the influence of the industrial sector on economic growth in Kediri City. Economic growth disparities between regions in Indonesia, including in East Java Province, contribute to imbalances in national development. One area experiencing low economic growth is Kediri City, which in 2023 recorded a growth rate of only 1.92%, ranking 37th out of 38 regencies/cities in East Java. Although the industrial sector contributes significantly to the city’s Gross Regional Domestic Product (GRDP) primarily due to the presence of PT Gudang Garam Tbk. economic growth has shown signs of slowing. This phenomenon raises concerns about the suboptimal potential for local economic development. The study employs a descriptive quantitative approach using time series data spanning two decades (2004–2023). Data analysis is conducted through multiple linear regression accompanied by classical assumption tests. The findings reveal that the presence of PT Gudang Garam Tbk. strengthens the influence of industrial variables—such as industrial GRDP, number of industrial enterprises, industrial labor, human capital, and dependency ratio—on economic growth. In contrast, when PT Gudang Garam is excluded from the model, the number of enterprises and industrial labor variables no longer show a significant effect. These results highlight the strategic role of PT Gudang Garam in reinforcing the industrial sector’s impact on economic growth in Kediri City.